MODERN INSTITUTIONAL APPROACHES IN THE DEVELOPMENT OF MULTILATERAL DIPLOMACY - Abdukarimov, Valikhon Abdukhamid ugli (Educational Research in Universal Sciences, 2024)
Multilateral diplomacy plays a crucial role in shaping the landscape of modern international relations. In essence, it involves the collaboration and interaction of three or more countries to address common challenges, negotiate agreements, and find solutions to global issues. The significance of multilateral diplomacy stems from its ability to foster cooperation, pool resources, and promote a more inclusive and effective approach to navigating the complexities of the contemporary world.